PERKEMBANGAN MATEMATIKA MUSLIM ABAD KE-8: KONTRIBUSI AL-KHAWARIZMI TERHADAP ALJABAR - Yulyanti Harisman; Putri Sania (Universitas Swadaya Gunung Jati., 2025)
In the 8th century, mathematics experienced development in the Islamic world, but there are still few studies that review in depth the contributions of muslim mathematicians in this period. There are many muslim figures or scientists who have a big contribution in the development of mathematics, one of them is Muhammad Ibn Musa Al-Khawarizmi. This study aims to analyze the influence of the work of muslim mathematicians, especially Al-Khawarizmi, on the development of algebra. The method used in this research is a qualitative method with a literature study approach. The instrument used in the research is a manuscript literature study, with the research subject covering the works of muslim mathematicians of the 8th century, and the data is analyzed using the descriptive narrative method. The results of this study are expected to increase knowledge about 8th century mathematics and further the importance of the contribution of muslim scientists in forming the basis of modern mathematics.